PERBANDINGAN EFEKTIVITAS MYOFASCIAL RELEASE TECHNIQUE DENGAN MUSCLE ENERGY TECHNIQUE PADA INTERVENSI ULTRASOUND DALAM MENURUNKAN DISABILITAS - Saraswati, Putu Ayu Sita; Juni Antari, Ni Komang Ayu; Angga Puspa Negara, Anak Agung Gede (Sport and Fitness Journal; Volume 7, No.3, September 2019DO - 10.24843/spj.2019.v07.i03.p01, 2019)
Introduction: A study shows the prevalence of musculoskeletal pain in the elbow most often diagnosed with elbow and forearm conditions is tennis elbow. Tennis Elbow, a common disease that can cause a decrease in productivity and economic losses. Treatment of physiotherapy that can be given for myofascial syndrome can be therapeutic modalities such as Ultrasound and manual therapy such as Muscle Energy Technique (MET) and Myofascial Release Technique (MRT). Method: This is an experimental study with pre and post test control group design. The number of samples was 24 people, which divided into 2 groups. Group I was given MRT with ultrasound, while Group II was given MET with ultrasound. Disability is measured by the Patient-Rated Tennis Elbow Evaluation Questionnaire. Results: Based on the results of the Paired Sample t-test in Group I and Group II the value of p <0.001 stated that there was a significant change after giving the exercise to each group. Furthermore, the comparison test between both groups used the independent sample t-test and p value <0.05. This shows that there are significant differences between groups. Conclusion: MRT further reduces disability due to tennis elbow compared to MET. Keywords: tennis elbow, disability, PRTEE, MET, MRT.